2018
DOI: 10.1186/s12909-018-1248-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Readiness for Interprofessional Learning with empathy, motivation and professional identity development in medical students

Abstract: BackgroundThe Readiness for Interprofessional Learning Scale is among the first scales developed for measurement of attitude towards interprofessional learning (IPL). However, the conceptual framework of the RIPLS still lacks clarity. We investigated the association of the RIPLS with professional identity, empathy and motivation, with the intention of relating RIPLS to other well-known concepts in healthcare education, in an attempt to clarify the concept of readiness.MethodsReadiness for interprofessional lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 57 publications
1
28
0
2
Order By: Relevance
“…Students in health care professions such as medicine, nursing, dentistry, and pharmacy gain expertise and skills that are important to performing their work, but one study found they were not sufficiently prepared to engage in teamwork in the form of interprofessional collaboration 4 . Interprofessional education (IPE) has been defined as occasions when individuals from two or more health professions “learn with, from, and about each other to improve collaboration and the quality of care.” 5 IPE was introduced to allow students from different health care professions to overcome barriers and preconceptions that exist among various health care groups in order to develop and improve teamwork and communication 4 , 6 . Many colleges and schools are seeking the best methods of providing IPE to their students to achieve learning outcomes, influence student perceptions, and change student behavior 7 , 8 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Students in health care professions such as medicine, nursing, dentistry, and pharmacy gain expertise and skills that are important to performing their work, but one study found they were not sufficiently prepared to engage in teamwork in the form of interprofessional collaboration 4 . Interprofessional education (IPE) has been defined as occasions when individuals from two or more health professions “learn with, from, and about each other to improve collaboration and the quality of care.” 5 IPE was introduced to allow students from different health care professions to overcome barriers and preconceptions that exist among various health care groups in order to develop and improve teamwork and communication 4 , 6 . Many colleges and schools are seeking the best methods of providing IPE to their students to achieve learning outcomes, influence student perceptions, and change student behavior 7 , 8 .…”
mentioning
confidence: 99%
“…5 IPE was introduced to allow students from different health care professions to overcome barriers and preconceptions that exist among various health care groups in order to develop and improve teamwork and communication. 4,6 Many colleges and schools are seeking the best methods of providing IPE to their students to achieve learning outcomes, influence student perceptions, and change student behavior. 7,8 To evaluate the effectiveness of these activities, the Interprofessional Collaborative Competency Attainment Survey (ICCAS) was developed to measure changes in self-reported competence in interprofessional care in IPE programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being internationally recognized as an important educational strategy, the integration of IPE into the standard curriculum remains a significant challenge [5]. Numerous barriers in implementation and achievement of positive IPE outcomes are described in the literature, and students' baseline attitudes such as stereotyping and prejudice are often cited as the biggest barrier of all [6][7][8]. Negative students' attitudes can be a major barrier in the learning process, and it is important to know the concept of "the readiness for IPE", that is, to assess students' attitudes towards IPE because it underlies the essence of accepting this educational strategy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous barriers in implementation and achievement of positive IPE outcomes are described in the literature, and students' baseline attitudes such as stereotyping and prejudice are often cited as the biggest barrier of all [6][7][8]. Negative students' attitudes can be a major barrier in the learning process, and it is important to know the concept of "the readiness for IPE", that is, to assess students' attitudes towards IPE because it underlies the essence of accepting this educational strategy [8]. The implementation of IPE requires a rigorous assessment that must start at the very beginning of curriculum development process [9,10].…”
Section: Introductionmentioning
confidence: 99%